2019
DOI: 10.1016/j.amepre.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Household Gun Ownership and Youth Suicide Rates at the State Level, 2005–2015

Abstract: Introduction: Determining whether the prevalence of gun ownership is associated with youth suicide is critical to inform policy to address this problem. The objective of this study is to investigate the relationship between the prevalence of household gun ownership in a state and that state's rate of youth suicide. Methods: This study, conducted in 2018, involved a secondary analysis of state-level data for the U.S. using multivariable linear regression. The relationship between the prevalence of household gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 40 publications
(45 reference statements)
5
56
0
Order By: Relevance
“…Model 2 contained the variables in Model 1 plus variables for alcohol consumption, unemployment rates, percent aboriginal population, and percentage of low income persons. These variables were examined as they have been included in regression models in previous studies as potentially associated with suicide rates [9,10,20]. The procedure of principal components was used to create a single variable containing the three variables as there existed a high degree of collinearity between variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Model 2 contained the variables in Model 1 plus variables for alcohol consumption, unemployment rates, percent aboriginal population, and percentage of low income persons. These variables were examined as they have been included in regression models in previous studies as potentially associated with suicide rates [9,10,20]. The procedure of principal components was used to create a single variable containing the three variables as there existed a high degree of collinearity between variables.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown an association between an increase in suicide rates and an increase in rates of poverty, alcohol consumption, and unemployment [10]. Interestingly, Knopov et al also found a positive association between suicide rates and the percentage of Aboriginal population per State in the United States [9]. In Canada, suicide rates amongst aboriginal people are 2 to 3 times higher than non-Indigenous Canadians and suicide rates amongst the Inuit in Northern Canada are the highest in the world at 10 times the overall rate for Canada [29].…”
Section: Plos Onementioning
confidence: 95%
See 2 more Smart Citations
“…Firearms are common in US households, with 41% of Americans reporting living in a household with a gun in 2017 4. Firearms are a particularly lethal method of suicide attempts,5 and access to firearms is associated with increased deaths from suicide 678. Firearm purchases have been specifically related to suicide—one study found the risk of suicide by firearms to be 57 times greater among Californians who had purchased a handgun in the past week compared with that in the general population of adults in the state 9.…”
Section: Introductionmentioning
confidence: 99%